Synthesis and preliminary evaluation of potential highly selective COX-2 inhibitors of some nonsteroidal anti-inflammatory derivatives - Alherwi, Mohammed; Almekhlafi, Sadik; Ahmed, Abdulghany H.; Ibrahim, Doa'a A. (Journal of Chemical and Pharmaceutical Research, 2016)
This work include design and synthesis of novel nonsteroidal anti-inflammatory(NSAI) derivatives, with potential selectivity cyclooxygenase 2(COX- 2) inhibitors from well-known NSAIDs ,to increase or at least maintain antiinflammatory activity, and decrease adverse effects resulting from COX-1 inhibition .Six compounds were synthesized ,(compound 2and 3) from aspirin with 4-(4-Fluorophenyl)isoxazol-5-amine and 6-chloro,2- aminobenzothiazole, (compound 6and 7) from diflunisal with 4-(4-Fluorophenyl)isoxazol-5-amine and 3-methyl-4- [3-(trifluoromethyl) phenyl]-5-isoxazolamine, (compound 9 and 10) from Ketoprofen with 2-Amino-5- (trifluoromethyl)1,3,4-thiadiazole and 2-Amino-5-ethyl 1,3,4-thiadiazole.Analysis by IR and 1H-NMR were performed and consistent with proposed synthesized structures. The preliminary pharmacological evaluation as anti-inflammatory activity test and ulcerogenic index screening were performed. From results of both test, we see most derivative showed good anti-inflammatory activity with range from46.5%(compound 2) to 36.2% (compound9) compared to 41% (standard) as %paw edema inhibition, but compound 2 and compound 6 showed ulcer index analogous to celecoxib a selective COX-2 inhibitors as a safe standard of gastric irritation.